Combining multicriteria decision making and geographic information system for assessing forest sustainability - Mendoza, G.A.; Prabhu, Ravi; Purnomo, H. (1999)
This paper describes an integrated framework for assessing the sustainability og managed forests. The framework builds on Geographic Information Systems (GIS) and Multiple Criteria Decision Making (MCDM). Sustainability of forests is assessed in terms of Criteria and Indicators (C & I) as proporsed by a number of national and international inititatives. MCDM procedures are used to help: 1) identify appropriate C & I; 2) prioritize and select a set of C & I to be used for sustainability assessment; and 3) develop a technique that can be used to estimate a "sustainability index". GIS on the other hand, will be used for: 1) generating and displaying needed information for the C & I assessment; 2) serving as the platform for doing spatial analysis; and 3) acting as the modeling environment for the estimation of a geographically-specific "sustainability index value". The integrated GIS-MCDM approach is participative, transparent, systematic, and objective. Mixed data (i.e, qualitative and quantitative) can be accomodated. Various methodologies dealing with multiple criteria, multiple decision makers, and the hierarchical structure of C & I will be described. Formal models will be described; each model designed to address different issues in the C & I hierarchy. The integrated approach will be applied and tested using actual forests managed and operated by a timber company in Indonesia.